1998
DOI: 10.1039/a805050c
|View full text |Cite
|
Sign up to set email alerts
|

Detection of incurred dihydrostreptomycin residues in milk by liquid chromatography and preliminary confirmation methods†

Abstract: An LC method for the determination of the aminoglycosides streptomycin (STR) and dihydrostreptomycin (DHS) in milk was developed/modified on the basis of published papers. Mean recoveries were 87 and 95% for STR and DHS, respectively. Recoveries are dependent on the concentration level and batch of solid-phase extraction columns used, and independent of fat content and homogenization. The relative standard deviations are 15.6 and 9.6% for STR and DHS, respectively, at a level of 100 micrograms kg-1. Limits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…1). The analysis of aminoglycosides are usually performed using pre-column [2][3][4][5][6][7][8] and post-column derivatization [9] methods, or other detections such as evaporative light scattering detection [10], pulsed electrochemical detection [11][12][13] and mass spectrometry [12,14,15]. Zhou et al [16] had reported an analytical method for veritlmicin in plasma and 1-fluoro-2,4-dinitrobenzene was used for derivatization.…”
Section: Introductionmentioning
confidence: 99%
“…1). The analysis of aminoglycosides are usually performed using pre-column [2][3][4][5][6][7][8] and post-column derivatization [9] methods, or other detections such as evaporative light scattering detection [10], pulsed electrochemical detection [11][12][13] and mass spectrometry [12,14,15]. Zhou et al [16] had reported an analytical method for veritlmicin in plasma and 1-fluoro-2,4-dinitrobenzene was used for derivatization.…”
Section: Introductionmentioning
confidence: 99%
“…14 Additionally, salts of heptasulfonic acid were employed as IP reagents in the SPE preconcentration of dihydrostreptomycin from milk 15,16 or streptomycin from various other foodstuffs. 17 This reagent was therefore chosen for further studies in our research, such as determination of breakthrough volume, analytical performance parameters and applicability of the method.…”
Section: Resultsmentioning
confidence: 99%
“…An IS was prepared by dissolving tobramycin in precipitating solution to give a concentration of 10 lg/mL. Aminoglycoside-free milk samples were mixed with five different levels (1,4,8,16, and 64 lg/mL) of 1 mL neomycin aqueous solution in 10 mL volumetric flasks and added with milk to the mark to prepare the final neomycin concentrations in milk over the range of 0.1 -6.4 lg/mL for analytical calibration. Milk samples (10 lL) were added in Eppendorf vials (500 lL) and then IS solution (5 lL) was added.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Recently, several types of SPE columns have been commonly used for extraction of aminoglycosides in bio-samples, such as a strong-cation exchanger [11,12], a weak-cation exchanger [13,14], an RP C18 [15,16], and a mixed model of an ion exchanger combined with RP [17]. Using SPE column, targeting analytes could be cleaned up, purified, and concentrated easily from a complicated matrix.…”
Section: Introductionmentioning
confidence: 99%